2021
DOI: 10.1186/s12913-021-07044-5
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of medical workers in China toward artificial intelligence in ophthalmology: a comparative survey

Abstract: Background In the development of artificial intelligence in ophthalmology, the ophthalmic AI-related recognition issues are prominent, but there is a lack of research into people’s familiarity with and their attitudes toward ophthalmic AI. This survey aims to assess medical workers’ and other professional technicians’ familiarity with, attitudes toward, and concerns about AI in ophthalmology. Methods This is a cross-sectional study design study. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 24 publications
(10 reference statements)
1
18
0
Order By: Relevance
“…Thirty-five included studies mentioned the knowledge level of physicians or medical students on clinical AI, of which 26 (74.29%) showed that participants lacked basic knowledge ( 16 19 , 23 , 25 , 26 , 28 46 ). Many physicians felt that the current training and educational tools, provided by their departments, were inadequate ( 47 , 48 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thirty-five included studies mentioned the knowledge level of physicians or medical students on clinical AI, of which 26 (74.29%) showed that participants lacked basic knowledge ( 16 19 , 23 , 25 , 26 , 28 46 ). Many physicians felt that the current training and educational tools, provided by their departments, were inadequate ( 47 , 48 ).…”
Section: Resultsmentioning
confidence: 99%
“…Forty-five included studies mentioned the views of physicians and medical students on clinical AI, and more than 60% of the respondents in 38 (84.44%) studies had an optimistic outlook regarding it ( 11 , 12 , 17 20 , 22 26 , 29 , 30 , 32 , 33 , 35 , 36 , 38 41 , 45 61 ). For example, 75% of 487 pathologists from 59 countries were enthusiastic about the progress of AI ( 11 ); 77% of 1271 dermatologists from 92 countries agreed that AI would improve dermatologic practice ( 19 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As suggested in the results, the intelligent diagnosis was less sensitive in groups 1 to 3 than in group 0, indicating further optimization and investigation of the diagnostic model. In future studies, the samples for model [24]. We expect more cooperation between ophthalmologists and experts in the field of artificial intelligence in attempt to define a more concise network model to reduce operating costs.…”
Section: Discussionmentioning
confidence: 99%
“…Fundus images with professional interpretation are a commonly accepted screening strategy for blindness prevention, with superior capability for in-person dilated eye examinations ( 5 ). However, the procedures for observing diabetic retinopathy confront challenges by factors correlated to execution, availability of professionals, and substantial financial sustainability ( 6 9 ). The automatic grading of diabetic retinopathy appears to have potential advantages in solving these obstacles, such as increasing efficiency, scalability, and coverage of examining procedures, extending applications in developed regions, and improving patient prevention by providing early diagnosis and referral.…”
Section: Introductionmentioning
confidence: 99%